THE SOCIAL DIMENSION OF SUSTAINABILITY FOR THE BUSINESS COMPETITIVENESS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Sustainability is a critical factor in business competitiveness, shaping corporate strategies and long-term market positioning. While the environmental dimension is well understood and widely adopted, the social dimension remains underexplored, leading to significant challenges. Issues such as employee well-being, diversity and inclusion, stakeholder engagement, fair labour practices, and ethical governance are often inadequately addressed, despite their substantial impact on business resilience and performance. The aim of this study is to examine the role of the social dimension of sustainability in enhancing competitiveness, emphasising its equal importance alongside environmental and economic considerations. Socially responsible practices strengthen brand reputation, foster customer loyalty, drive innovation, and improve employee productivity - factors essential for maintaining a competitive edge in modern markets. The study employs a methodological approach based on primary and secondary data analysis, drawing insights from academic literature, policy documents, corporate sustainability and Environmental, Social, Governance (ESG) reports, and sustainability expert interviews to provide a practical perspective on emerging trends, challenges, and best practices in implementing social sustainability initiatives in a real business environment. This multi-source approach ensures a comprehensive understanding of the current state and future directions of social sustainability of businesses. This study contributes to the growing discourse on sustainable business practices by demonstrating that social sustainability is not merely an ethical consideration but a fundamental element of corporate success. Enterprises face challenges related to defining, quantifying, and operationalising social sustainability. At the same time the results of the study show that European Sustainability Reporting Standards provide a comprehensive framework for corporate social sustainability initiatives of enterprises. The study’s results highlight the need for a structured, data-driven approach to defining and measuring the social dimension of sustainability for small and medium enterprises and serve as evidence-based methodological framework for further exploration of social sustainability as a core driver of business competitiveness.